Bereavement support guidelines for caregivers in palliative care: a scoping review - Coelho, Alexandra; Albuquerque, Sara; Neto, David Dias (Frontiers in Psychology, 2025)
BackgroundPalliative care teams’ support practices for bereavement vary substantially. Clinical guidelines are needed to promote concerted, evidence-based intervention. The goal of the present study is to identify and synthesize the principles and clinical guidelines that ensure best practices in bereavement support for family caregivers accompanied in palliative care.MethodsA scoping review was conducted based on a systematic search of articles in academic databases (EBSCO, PsycINFO, PubMed, Web of Science, Psychology and Behavioral Sciences Collection, Scopus) and Google (2010–2024). The review included articles focused on the principles, guidelines, and clinical recommendations for bereavement support for adult family caregivers in palliative care. Quality appraisal of guidelines was conducted using the AGREE II instrument.ResultsOf the 1,489 references identified, 20 documents were included, mostly governmental or institutional norms and clinical guidelines from gray literature. Quality appraisal revealed gaps in evidence selection, resource implications, updates and monitoring criteria. Eight fundamental principles were identified, from which several clinical guidelines were derived, organized according to the moments of assessment and intervention throughout the bereavement process, including pre and post-death period: (1) organizing support for the family caregiver; (2) assessing needs and establishing a care plan; (3) ensuring information and support for the family caregiver; (4) preparing for death; (5) support at the time of death; and (6) bereavement support post-death. In addition to universal support and information measures, regular assessment procedures should be adopted for timely referrals based on individual needs.DiscussionThese guidelines cover the temporal variation of care and the multidimensional and multiple-actor nature of palliative care. Implementing these guidelines and evaluating their impact will allow for the standardization of best practices and improve the quality of bereavement support in palliative care.